2012
DOI: 10.1002/j.1681-4835.2012.tb00382.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐Government Service Quality: A Qualitative Evaluation in the Case of Saudi Arabia

Abstract: Government website services comprise awareness programs for their citizens and others, information distribution, and perhaps data collection, online enquiries, and submissions for regulatory or funding purposes. Quality of service is fundamental to public acceptance and use of e-government websites, although this aspect is frequently overlooked during the design and implementation stages of online public services. Besides transparency, ease of navigation and comprehensive information, these websites require ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
24
0
2
Order By: Relevance
“…Service quality is also affected by the ease of use , which refers to how easy it is to navigate and follow service delivery steps (Alanezi et al, ). Papadomichelaki and Mentzas () consider navigation, personalization, and technical efficiency as ease of use constructs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Service quality is also affected by the ease of use , which refers to how easy it is to navigate and follow service delivery steps (Alanezi et al, ). Papadomichelaki and Mentzas () consider navigation, personalization, and technical efficiency as ease of use constructs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Availability The quality of being at the users' disposal all of the time (Al-Busaidy & Weerakkody, 2009;Anwer et al, 2016;Papadomichelaki & Mentzas, 2012;Verdegem & Verleye, 2009) 3. Information quality The degree to which information is ready, complete, clear, and accurate (Alanezi, Mahmood, & Basri, 2012;DeLone & McLean, 2003;Kaisara & Pather, 2011;Okunola & Rowley, 2013;Rasyid & Alfina, 2017;Verdegem & Verleye, 2009) 4. Awareness Knowledge of existing services (Ahmed et al, 2015;Alawneh et al, 2013;Anwer et al, 2016;Sharma & Mishra, 2017;Sigwejo & Pather, 2016;Verdegem & Verleye, 2009)…”
Section: Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the commonly ignored aspect of eGovernment services implementation quality, [18] more so in developing countries, it is argued that the quality of services in government websites is a key element for the adoption (acceptance) of ICT within citizens. Research has explored many quality aspects of offered online services, such as the degree of information comprehension, ease of navigation, transparency, system availability, personalization, processing time, interactivity, credibility, security, and privacy.…”
Section: Ict E-gov and Older Adults In The Middle Eastmentioning
confidence: 99%
“…Furthermore, a research conducted in Saudi Arabia found that citizens would consider e-Government services as quality services only when these services meet their needs [18]. In terms of this study, quality aspects of online services were included in the constructs of perceived website assistance (PWA), complexity (COMP), and perceived cyber risk (PCR).…”
Section: E-government Servicesmentioning
confidence: 99%